2017
DOI: 10.1016/j.jad.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-regression of the prevalence and incidence of perinatal depression

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
659
10
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 998 publications
(789 citation statements)
references
References 48 publications
32
659
10
19
Order By: Relevance
“…The prevalence of moderate-severe depression found in our study is in line with estimates from non-migrant women in other LMIC. For example, Woody et al (2017) found a pooled antenatal prevalence of 19.2% and postnatal prevalence of 18.7% in low-income settings [3]. Our estimates are also in line with findings from a meta-analysis of migrant women from LMIC who resettled in HIC, which reported pooled estimates of 17% for major depressive disorder and 31% for any depressive disorder [13].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The prevalence of moderate-severe depression found in our study is in line with estimates from non-migrant women in other LMIC. For example, Woody et al (2017) found a pooled antenatal prevalence of 19.2% and postnatal prevalence of 18.7% in low-income settings [3]. Our estimates are also in line with findings from a meta-analysis of migrant women from LMIC who resettled in HIC, which reported pooled estimates of 17% for major depressive disorder and 31% for any depressive disorder [13].…”
Section: Discussionsupporting
confidence: 87%
“…Evidence consistently suggests that prevalence is higher in low-and middle-income countries (LMIC), with estimates ranging from 10. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].3% in LMIC compared with 7.4-19.2% in high-income countries (HIC) [1,3,4]. Untreated perinatal depression has been associated with a number of significant adverse outcomes including negative health behaviours in pregnancy [1], subsequent chronic and recurrent depression [1,2], impaired ability to work and provide care, relationship breakdown [2,5] and suicidean important contributor to maternal deaths globally [6,7].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…For example, globally approximately 10% of pregnant women were estimated to suffer from depression,1 with prevalence rates of 15.6% in low-income and lower-middle-income countries 8. A recent meta-analysis has reported a 19.2% prevalence of antenatal depression in low-income and middle-income countries 58. The higher prevalence found in our meta-analysis may reflect a high prevalence of risk factors within the pregnant population of the region as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal depression, the onset of depression during pregnancy or within the first four weeks after giving birth (American Psychiatric Association, 2013), is a global health concern affecting an estimated 11.9% of women (Woody, Ferrari, Siskind, Whiteford, & Harris, 2017) and their infants whose cognitive, emotional, and behavioral development may be impaired (Hoffman, Dunn, & Njoroge, 2017;Stein et al, 2014). Decades of research suggest that the etiology of perinatal depression is complex, and that perinatal depression risk is modulated by a range of biological (e.g., endocrine, inflammatory, genetic) and psychosocial (e.g., stress, social support, relationship quality) factors (e.g., Yim, Tanner Stapleton, Guardino, Hahn-Holbrook, & Dunkel Schetter, 2015).…”
Section: Introductionmentioning
confidence: 99%